Psychosocial factors associated with physical activity in ambulatory and manual wheelchair users with spinal cord injury: a mixed-methods study. Issue 2 (16th January 2017) - Martin Ginis, Kathleen A.; Papathomas, Anthony; Perrier, Marie-Josée; Smith, Brett; ,
Abstract: Purpose : To identify psychosocial factors which explain lower levels of leisure time physical activity (LTPA) in persons with spinal cord injury (SCI) who are ambulatory relative to those who use manual wheelchairs. Method : For the quantitative study component, 347 adults with SCI (78% male; M age = 47.7) completed baseline measures of LTPA attitudes, subjective norms, perceived behavioural control and intentions. Six months later, LTPA was assessed. The qualitative component involved semi-structured interviews with six ambulant adults with SCI (five male, M age = 52.8) addressing LTPA experiences with an emphasis on barriers and facilitators. Results : Ambulatory individuals had poorer attitudes towards LTPA than chair users ( p = 0.004). Their attitudes had significant indirect effects on LTPA, through intentions. Perceived behavioural control was a significant negative predictor of LTPA. Qualitative analysis revealed three themes: an underestimated disability, low wheelchair skill self-efficacy and experiencing chronic pain. Conclusions : Poorer attitudes towards LTPA may partially explain why ambulatory individuals are less active. The qualitative and quantitative data suggest ambulators are an often-overlooked subgroup in need of targeted resources to enhance their attitudes, wheelchair skill self-efficacy and awareness of LTPA opportunities. Implications for Rehabilitation: Rehabilitation practitioners must be sensitive to the unique needs of spinal cord injured individuals who are ambulatory, and tailor physical activity promotional strategies to suit the needs of this distinct group. Lack of wheelchair skills is a participation barrier for ambulators; ambulators should be introduced to activities that do not require wheelchair use, such as swimming, hand-cycling and adapted forms of circuit training. Strategies that encourage wheelchair skill development in non-wheelchair using ambulators, may increase physical activity opportunities for this segment of the spinal injured population.